Automatic Gate Prototype Based on Microcontroller of Atmel ATMega16 - Anna Nur Nazilah Chamim; Raja Erwanto; Agus Jamal (Universitas Muhammadiyah Yogyakarta, 2017)
Aside from being a place of lectures, UMY also has several business units such as building rental, bus rental, auto care, and drinking water production. From the activities of UMY's business unit caused the number of outside vehicles entering UMY. The public vehicle does not have RFID as well as the UMY's internal civitas. Currently still using manpower to provide parking cards and open the door. In this study, a prototype of an automated parking system can provide a parking card and open the entrance. This prototype uses a switch as a sensor, a microcontroller as a controller, LCD as a guide display for the model of vehicle that will enter, and motor servo DC as the driver of parking doors. The entire circuit is able to form a prototype automatic parking door at UMY